Elaborating the Role of Narrative and Self-Determination Theory in Video Game Design Research - Lu, Amy Shirong; Moller, Arlen C (Interacting with computers, 2024)
Narratives, defined as stories involving two or more events arranged in a chronological or causal sequence, are fundamental and ubiquitous characteristics of human communication and serve as an integral feature of many video games. Moreover, narratives can be understood in nuanced ways through the lens of Self-Determination Theory (SDT). Yet, the intersection of SDT and video game narratives has been surprisingly underexplored. This article reviews research on narrative media and examines how narratives can be integrated into games from the perspective of SDT and potential boundary conditions. We then explore how concepts from narrative theories and SDT can be integrated. The goal of this integration is to help guide future game design and identify new questions for future research related to: (1) the integration of parable narratives in video games, specifically parable narratives featuring characters' personal transformation and growth and (2) predicting which video games people choose and prefer. We argue that scholars working with narrative theories and SDT can collaborate to advance video game research.